Intention to report misconduct of the Royal Malaysian Police: Examining perceived offence seriousness, perceived disciplinary fairness and perceived legitimacy - Khan, Norziaton Ismail (International journal of police science & management, 2024)
The intention to report misconduct is the inclination of police officers to disclose wrongdoing perpetrated by other officers, whereas the code of silence is an unwritten policy prohibiting officers from reporting the misbehaviour of their colleagues. Hence, officers have the choice either to remain silent or to report any misconduct by their colleagues. This article investigates the determinants of the intention to report misconduct by Royal Malaysian Police (RMP) officers from the commercial crime investigation department. Organizational theory is used to form the framework and develop the hypotheses. Three hypotheses are developed concerning the intention to report RMP officer misconduct using three elements: perceived offence seriousness, perceived disciplinary fairness and perceived legitimacy. Face-to-face and online survey questionnaires were used as data collection methods. In total, 170 questionnaires were distributed, and 151 completed questionnaires were useable. The questionnaire contained four scenarios illustrating various forms of misconduct; each contained seven questions measuring police officers’ perception and assessment of their intention to report, perceived seriousness of the offence, perceived disciplinary fairness and other intentions to report. Ordinal logistic regression analysis revealed that perceived offence seriousness and perceived legitimacy had a strong positive relationship with officer intentions to report misconduct. This study has important implications for national and international policymakers to find out how well officers understand their agency's rules on misconduct as well as their opinions about the seriousness of the different types of misconduct, the appropriate discipline for the misconduct and their willingness to report the behaviour.